In the market for humane rights - Inglis, Fred (Times Higher Education, 2018)
Keywords: Human rights; Moral Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); Rogan, Tim; austerity (economics); book review; cultural history; nonfiction

An Economic Prophet for Our Time - Iber, Patrick (The Chronicle of Higher Education, 2017)
Karl Polanyi knew the market couldn’t solve all ills. History is proving him correct.
Keywords: Karl Polanyi: A Life on the Left (Book); SANDERS, Bernie; TRUMP, Donald

Moving targets: Carbon pricing, energy markets, and social movements in Australia - Pearse, Rebecca (Environmental Politics, 2016)
Reporting on the origins and directions of social movement strategy on climate and energy issues in the last decade, the shifts in ‘climate movement’ practice are discussed using a neo-Polanyian account of the political economy of climate change combined with sociological analysis of the strategic decisions campaigners reported making. Since the mid-2000s, Australia’s climate movement has been engaged in three concurrent arenas of political contestation. The longest-standing arena of movement activity has been negotiations over climate policy. More recently, activists and communities are engaged in a struggle over the expansion of fossil fuels. A third contest has been waged over the present and future position of renewable energy technologies in Australia’s electricity market. In the wake of climate policy failure, energy campaigns have been deepened, and it seems that a broader energy justice agenda is being forged. New strategic dilemmas are visible in the field.
Keywords: Australia; carbon pricing; climate policy; climatic changes; economics; energy industries; energy markets; fossil fuels; renewable energy sources; social movements

Herculean efforts are not enough: diversifying the teaching profession and the need for systemic change - Schmidt, Clea (Intercultural Education, 2015)
Internationally educated teachers (IETs) seeking to resume their careers in Canada often demonstrate tremendous endurance, fortitude, and resilience in the process of navigating their new professional landscapes, yet neoliberalism and the myth of meritocracy obscure the pervasive systemic barriers characterizing their professional experiences. Critical action research undertaken with graduates of an academic and professional bridging program for IETs in Manitoba reveals a complex interplay of challenges with respect to diversifying the teaching force in intercultural settings. Data collected with IETs seeking full-time teaching positions suggest resuming their careers is by no means guaranteed for many IETs who, in spite of what can be deemed herculean efforts to follow the advice of mentors and make themselves as ‘marketable’ as possible, continue to face significant barriers to employment in a context largely characterized by an over-supply of qualified applicants. Guided by Cummins’ work on collaborative relations of power and a Polanyian critique of economic determinism, my analysis illuminates a multi-pronged systemic approach that has the potential to help ensure the numerous contributions of IETs in Canadian schools can be fully realized.
Keywords: Canada; career development; collaborative relations of power; critical theory; economic determinism; equity; internationally educated teachers; professional education; systemic barriers; teacher development; teachers

Emancipation, marketisation, and social protection: the female subject within vocational training policy in Canada, 1960–1990 - Pullman, Ashley (Gender and Education, 2015)
This paper examines Canadian federal and cross-provincial higher education policy from 1960 to 1990, a critical time when provisions for vocational and adult training came under the auspices of governmental concern, justified under both an economic rationale and as a way to address persistent forms of inequality. The problematisation of skill during this period had particular gendered implications, as addressing inequality through education subsidies intersected with the perceived training needs of employers and the market. Employing Nancy Fraser's theory of a ‘triple movement’, the following paper ‘takes stock’ of how the three political forces of social movements, marketisation, and social protection have shaped gendered discourses of education and training, the implications for which are of continued relevance to those trying to understand the education and training within the contemporary neo-liberal state.
Keywords: Canada; education policy; gender; historical sociology; history; institutional analysis; social protection; vocational education and training; welfare; workfare

Group learning as relational economic activity - Saito, Eisuke; Atencio, Matthew (Educational Review, 2014)
The purpose of this paper is to discuss group learning in line with economic perspectives of embeddedness and integration emanating from the work of Karl Polanyi. Polanyi’s work defines economy as a necessary interaction among human beings for survival; the economy is considered inextricably linked from broader society and social relations rather than autonomous and driven by self-interest in free market conditions. He specifically outlines three key forms of integration that are crucial to economic stability, involving the notions of reciprocity, redistribution, and exchange. These patterns of integration are described as key elements that co-mingle within and structure contemporary group learning within classrooms.
Keywords: collaborative learning; cooperative learning; economic activity; education; embeddedness; embeddedness (socioeconomic theory); group learning; group work in education; reciprocity (commerce); social integration

Does the human capital discourse promote or hinder the right to education? The case of girls, orphans and vulnerable children in Rwanda - Balsera, Maria Ron (Journal of International Development, 2011)
This paper studies the implications of considering education as a human right and examining it through the lens of the human capital discourse. It uses Polanyi's idea of decommodification, as discussed by Offe and Esping-Andersen, as well as Foucault's concept of governmentality, to analyse the changes that are taking place in the education sector in post-genocide Rwanda. It focuses on the consequences of the human capital discourse for girls, orphans, children with disabilities and Batwa in Rwanda. The paper concludes that although the human capital discourse has brought attention and resources to education, the situation has worsened for some marginalised groups leading to growing inequalities and discrimination. Copyright © 2011 John Wiley & Sons, Ltd.
Keywords: Rwanda; commodification; decommodification; human capital; neoliberal governmentality; right to education

"A Market Where We All Fit" Adult Education and the Fair Trade Movement - Sumner, Jennifer (Canadian Journal for the Study of Adult Education, 2008)
The global market continues to create the "great and permanent evils" so well outlined by Karl Polanyi in his book, The Great Transformatioit His description of the destructive effects of the emerging self-regulating market during the Industrial Revolution is reflected today in the ongoing erosion of social, environmental, and economic sustainability in both the North and the South. In this downward spiral of life parameters, fair trade opens up the possibility of a market where we all fit, not where we all ultimately fail. Adult education has a vital role to play in opening up spaces where fair trade can prosper and grow, thus contributing to a second great transformation to a more sustainable society.
Keywords: Great Transformation, The (Book); POLANYI, Karl, 1886-1964; adult education - economic aspects; international trade; self-regulation of industries; unfair competition